Propuesta de la teoría OUCHI para mejorar la gestión empresarial de las empresas Agroindustriales de la provincia de Virú - Pérez Sosaya, Julio Omar (2011)
Herinvestigation accomplished at the sector of the agroindustrial companies of Vir's province, meeting than the organizations of the sector application has been more than the theory X, which himself I determine that it is necessary to accomplish a proposal, the implementation of the theory Z in the aforementioned organizations. Coming into question the following problem As the management of the agroindustrial companies of Viru's province would be able to get better?, Getting to the following hypothesis: Insofar as Ouchi applies over himself the theory, will the management of the agroindustrial companies of Viru's province be able to get better?.In the obtained results it is noticed that they apply decision making but in the personal aspect, since the ones that take the decisions are the same proprietors and they do not want to see displaced persons, in like manner that communication is vertical, meeting also than incentives investors see it like an expense than an investment. Finally himself I present a proposal of how the management of her would be able to improve agroindustrial companies of Viru's province, by means of the theory Ouchi.